Genetic Reassortment Among the Influenza Viruses (Avian Influenza, Human Influenza and Swine Influenza) in Pigs - Hewajuli, Dyah Ayu; Dharmiayanti, Ni Luh Putu Indi (Indonesian Animal Sciences Society, 2012)
Influenza A virus is a hazardous virus and harm to respiratory tract. The virus infect birds, pigs, horses, dogs, mammals and humans. Pigs are important hosts in ecology of the influenza virus because they have two receptors, namely NeuAc 2,3Gal and NeuAc 2,6Gal which make the pigs are sensitive to infection of influenza virus from birds and humans and genetic reassortment can be occurred. Classical swine influenza H1N1 viruses had been circulated in pigs in North America and other countries for 80 years. In 1998, triple reassortant H3N2 swine influenza viruses that contains genes of human influenza A virus (H3N2), swine influenza virus (H1N1) and avian influenza are reported as cause an outbreaks in pigs in North America. Furthermore, the circulation of triple reassortant H3N2 swine influenza virus resulting reassortant H1N1 swine influenza and reassortant H1N2 swine influenza viruses cause infection in humans. Humans who were infected by triple reassortant swine influenza A virus (H1N1) usually made direct contact with pigs. Although without any clinical symptoms, pigs that are infected by triple reassortant swine influenza A (H1N1) can transmit infection to the humans around them. In June 2009, WHO declared that pandemic influenza of reassortant H1N1 influenza A virus (novel H1N1) has reached phase 6. In Indonesia until 2009, there were 1005 people were infected by H1N1 influenza A and 5 of them died. Novel H1N1 and H5N1 viruses have been circulated in humans and pigs in Indonesia. H5N1 reassortant and H1N1 viruses or the seasonal flu may could arise because of genetic reassortment between avian influenza and humans influenza viruses that infect pigs together. Key words: influenza viruses, swine, genetic reassortment